Prices in Motion: Schumpeter’s Contribution to Price Theory - Bloch, Harry (Centre for Research in Applied Economics, 2014)
Schumpeter distinguishes between the circular flow of economic activity and economic development. The former is characterised by equilibrium, while the latter involves discontinuous change that induces business cycles. Schumpeter argues that with development prices are generally in motion. Schumpeter’s theory of the business cycle has been heavily criticised. Specific criticisms relating to his price theory include its characterisation of prices stabilising near the Walrasian competitive equilibrium for a stationary economy and its prediction of a downward trend in prices over the longest cycles. This paper reviews Schumpeter’s theory and the critiques before suggesting a way forward to a revised theory of prices in motion.